Status of the AMoRE experiment searching for neutrinoless double beta decay using low-temperature detectors - Jo, Hyon Suk; Choi, S.; Danevich, F. A.; Fleischmann, Andreas; Jeon, J. A.; Kang, C. S.; Kang, W. G.; Kim, G. B.; Kim, H. J.; Kim, H. L.; Kim, I.; Kim, S. K.; et al. (Journal of low temperature physics, 2018)
The goal of the Advanced Mo-based Rare process Experiment (AMoRE) is to search for the neutrinoless double beta decay of 100100^{100}Mo using low-temperature detectors consisting of Mo-based scintillating crystals read out via metallic magnetic calorimeters. Heat and light signals are measured simultaneously at millikelvin temperatures, which are reached using a cryogen-free dilution refrigerator. The AMoRE-Pilot experiment, using six 100100^{100}Mo-enriched, 4848^{48}Ca-depleted calcium molybdate crystals with a total mass of about 1.9 kg, has been running in the 700-m-deep Yangyang underground laboratory as the pilot phase of the AMoRE project. Several setup improvements through different runs allowed us to achieve a high energy resolution and an efficient particle discrimination. This article briefly presents the status of the AMoRE-Pilot experiment, as well as the plans for the next, larger-scale, experimental stages.